Obucenie junych futbolistov technike vedenija mjaca i obvodki s primeneniem interaktivnogo trenažernogo kompleksa - Afonshin, V. E.; Drandrov, G. L.; Konovalov, I. E. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of a new training system (TS) for junior (10-11 year-old) footballers to master ball handling and dribbling skills - designed using the modern computerized interactive video imaging system. The TS generates a variety of static and dynamic images different in content and shapes including different zones, points, routes, corridors, circles, squares etc. on the game field. The TS also makes it possible to generate special training and progress test exercises variable in the spatial and temporal terms - to successfully train the junior footballers in a wide variety of simulated game situations - with/ without the ball and with/ without opposition that is rated and controlled by the coach by manual or software tools customizable to the individual skills and fitness. The TS gave the means to design a set of special training practices and identify the process management and practical conditions for the junior footballers to successfully master the ball handling and dribbling skills. The new training system was tested beneficial as verified by the junior footballers` progress in the ball handling and dribbling skills.